Improving Employee Competence in Food Logistics Services in Cirebon City - Adinda; Wulandari, Sri (Syntax Corporation Indonesia, 2026)
Perum Bulog plays a strategic role in maintaining national food security, but its implementation has not been optimal because employee competencies still need to be improved. Therefore, human resource capacity building is an important factor in strengthening Perum Bulog's performance. This study aims to identify employee competencies in improving food logistics services, as well as obstacles and implementation efforts at Perum Bulog Cirebon. This study used a qualitative descriptive method with an empirical approach. The main informant is the Head of Perum Bulog Cirebon Branch with supporting informants being employees and work partners. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The research refers to (Spencer & Spencer, 1993) competency theory, which includes motive, traits, self-concept, knowledge, and skills. The results show that employee competency is not yet optimal, especially in terms of knowledge and skills, which is influenced by training that is not yet routine and is still centralized at the head office. Other obstacles include the incompatibility of employees' educational backgrounds, complaints from partners about the quality of rice, and manual administration. Efforts made include branch-based training, strengthening rice quality control, and providing online administrative verification services. Improving employee competency is key to improving food logistics services at Bulog Cirebon.